RESPON BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) ASAL KABUPATEN BENGKALIS TERHADAP BEBERAPA TAKARAN PEMUPUKAN N, P DAN K - Siti Norkhalimah; Idwar '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to determine the response of Bengkalis local rice to N, P and K fertilizer. The research was conducted in screen house, experiment garden Faculty of Agriculture, University of Riau, Pekanbaru. The research conducted 7 months start from June 2013 until January 2014. The research conducted experiments using completely randomized design (CRD) consist of 2 factors and 3 replications. Least Significant Different (LSD) used for mean separations. First factor was varieties of Dara, Kulit Manis and Inpago 5, the second factor was N, P and K fertilizer. The result showed that the variety of Dara was significantly affected in are panicle emergence time, time of harvest, panicle length, weight of 100 seeds and percentage of seeds parameters. Variety of Kulit Manis was significantly affected in seed weight of panicle and weight of dried plant parameters. Variety of Inpago 5 was significantly affected in seed weight of panicle, seed weight of group and weight of dried plant parameters. There are 3 varieties, Inpago 5 showed higher production and better than varieties of local rice. Dara variety can further develop as a good local. Key words: fertilizer of N, P and K, productivity, responses, varieties of upland rice